PTEN PDZ-binding domain suppresses mammary carcinogenesis in the MMTV-PyMT breast cancer model. (28th August 2018) - Yan, Mingfei; Wang, Yubing; Wong, Chi Wai; Or, Penelope Mei-Yu; Wong, Kin Lok; Li, Lisha; Many, Alexander M.; Guan, Hong; Khoo, Ui Soon; Chan, Andrew M.
Abstract: Phosphatase and tension homolog (PTEN) is a potent tumor suppressor that possesses a PDZ-binding domain (PDZ-BD) at the end of its carboxyl terminus, whose functions during tumorigenesis remains unclear. Here, we crossed a mouse strain with germline deletion of PTEN PDZ-BD with MMTV-PyMT breast cancer model, and found that knockout (KO) mice display normal development of mammary glands, but have both increased breast tumorigenicity and lung metastasis. Orthotopic allograft experiments suggest the loss of PTEN PDZ-BD in breast cancer cells rather than in tumor microenvironment plays a prominent role in increasing tumor burden. Through RNA-sequencing, we observed a significant downregulation of myoepithelial marker genes in both KO primary breast cancer and orthotopic allografts. Moreover, these myoepithelial marker genes are significantly downregulated in human breast cancer tissues, and are associated with poorer clinical prognosis. In addition, several homeobox genes were also identified to be downreguated in KO breast cancer, whose expressions showed significant positive correlation with myoepithelial marker genes. Overall, our findings suggest a novel tumor suppressive role of PTEN PDZ-BD in a murine model of breast cancer, and the mechanism involves the dysregulation of homeobox genes which may result in defective myoepithelial differentiation in breast cancer cells. Highlights: A mouse strain with germline deletion of PTEN PDZ-binding domain (PDZ-BD) was generated. Loss of PTEN PDZ-BD results in larger mammary ducts but does not interfere with normal development of mammary glands. PTEN PDZ-BD suppresses MMTV-PyMT breast carcinogenesis and lung metastasis. Myoepithelial specific marker genes are significantly downregulated in PTEN PDZ-BD KO breast cancer. Downregulation of myoepithelial marker genes is correlated with downregulation of several homeobox genes in KO breast cancer.